ANALISIS KESESUAIAN LAHAN TINGKAT SATUAN PEMUKIMAN MENGGUNAKAN AUTOMATED LAND EVALUATION SYSTEM (ALES): STUDI KASUS RANTAU PANDAN SP-1, PROVINSI JAMBI - Widiatmaka Widiatmaka; Setyardi Pratika Mulya; Marwan Hendrisman (Graduate School Bogor Agricultural University (SPs IPB), 2012)
Landuse planning according to biophysical and economical land suitability as well as basic allocation for transmigration should be done in order to improve the well-being of transmigrants. Suitability should be analyzed for the selection of commodities which are the most appropriate biophysically and profitable economically. The study was done in the settlements unit of Rantau Pandan SP-1, Jambi Province. The study was conducted to determine the suitability of each part of land for cultivation of food crops, vegetables and perennial crops and to see the biophysical suitability and economical feasibility. The goal is to recommend the most appropriate type of cultivation. This study integrate the Arc-View GIS and Automated Land Evaluation System (ALES) in the analysis of land suitability. The results showed that four agricultural commodities were observed showing land suitability class domination of S3 (marginally suitable) with the most dominant limiting factors were erosion and nutrient retention. The results of the analysis have been used for the determination of land use recommendations in the transmigration sites, presented spatially. Recommendations given based on the results of the analysis were not always in line with the land use recomended by government on dry land transmigration. Nonetheless, these results was suggested to be applied, either by considerations of conservation land and the consideration of economic benefit and farmers welfare. Key words: Land evaluation, transmigration, dry land farming, geographic information system